2021
DOI: 10.7554/elife.58430
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation meta-analysis reveals cellular alterations in psychosis and markers of treatment-resistant schizophrenia

Abstract: We performed a systematic analysis of blood DNA methylation profiles from 4,483 participants from seven independent cohorts identifying differentially methylated positions (DMPs) associated with psychosis, schizophrenia and treatment-resistant schizophrenia. Psychosis cases were characterized by significant differences in measures of blood cell proportions and elevated smoking exposure derived from the DNA methylation data, with the largest differences seen in treatment-resistant schizophrenia patients. We imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(99 citation statements)
references
References 82 publications
5
94
0
Order By: Relevance
“…A systematic epigenome-wide association studies (EWAS) to analyse methylation profiles of DNA collected from blood sampled of seven different cohorts have identified 95 differentially methylated positions (DMPs) associated with psychosis and 1048 DMPs associated with treatment-resistant schizophrenia. This study also highlights the identification of potential biomarker candidate genes as well as open future avenues towards successful development of therapeutics [ 35 ].…”
Section: Maternal Dietary and Supplementary Intakesmentioning
confidence: 99%
“…A systematic epigenome-wide association studies (EWAS) to analyse methylation profiles of DNA collected from blood sampled of seven different cohorts have identified 95 differentially methylated positions (DMPs) associated with psychosis and 1048 DMPs associated with treatment-resistant schizophrenia. This study also highlights the identification of potential biomarker candidate genes as well as open future avenues towards successful development of therapeutics [ 35 ].…”
Section: Maternal Dietary and Supplementary Intakesmentioning
confidence: 99%
“…Indeed, of the 641 context enriched genes, 114 were missed in the larger analysis illustrating how genes and terms associated with immune responses masked our ability to detect a greater depth of neurologically relevant signals. By way of example, we discovered a modest but significant overlap (Fisher's Exact Test p = 0.0492) between our context enriched gene set and genes highlighted in a recent meta-analysis of differentially methylated positions associated with psychosis, schizophrenia and treatmentresistant schizophrenia 49 which was not detectable using the full DE gene set.…”
Section: Recovery Of Neurologically Relevant Annotations Is Aided By a Novel Context Enrichment Approachmentioning
confidence: 77%
“…GO enrichment analysis was then performed on this subset per above using both the full GO ontology and NIGO, a neuro-immune focused GO subset developed using a clipping approach based on domain-specific relevance 47 obtained from BioPortal 70 . We obtained the list of genes with differentially methylated positions associated with psychosis, schizophrenia and treatment-resistant schizophrenia from supplementary material in Hannon et al 49 The expected overlap between this set and our context enriched set was assessed using Fisher's Exact Test assuming an estimated background frequency of 658/20,648 for SZassociated methylated mouse genes.…”
Section: Functional Analysismentioning
confidence: 99%
“…In some studies, epigenetic variation induced by environmental exposure has been hypothesized as another mechanism by which non-genetic factors can affect risk for neuropsychiatric disorders including schizophrenia as well as efficacy of antipsychotic medication [103]. Hannon et al have shown that there are differences in DNA methylation patterns in patients with schizophrenia, taking into account patients' smoking status as well as drug treatment with clozapine or other antipsychotic drugs [104]. Much more research is required in order to fully understand the influence of smoking behavior on DNA methylation and possibly also on the efficacy of antipsychotic drugs, especially in treatment-resistant schizophrenia.…”
Section: Smoking-associated Pharmacokinetic Changes Due To Other Mechanismsmentioning
confidence: 99%